Navigating Adolescent Happiness: Exploring Determinants, Obstacles, and Implications from Recent Literature (2021-2025) - Hevitriana; Mira Ariyani; Deasyanti; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
This study explores key factors influencing adolescent happiness through a narrative literature review. Adolescence is a vulnerable phase marked by significant biological, psychological, and social transitions, making happiness a vital component for long-term well-being and healthy development. The review analyzed 20 peer-reviewed articles published between 2021 and 2025. Findings indicate that adolescent happiness is shaped by three main domains: (1) individual psychological factors such as emotion regulation, gratitude, optimism, religiosity, self-acceptance, self-esteem, character strengths, help-seeking behavior, and emotional intelligence; (2) social and relational factors, particularly the quality of relationships with parents and peers; and (3) lifestyle factors, including sleep quality, physical activity, and patterns of social media use. In addition, several barriers were identified, such as academic stress, interpersonal difficulties, and unhealthy daily habits. These findings suggest the importance of integrated intervention strategies that address internal psychological skills, enhance interpersonal relationships, and promote healthy lifestyle choices. The study contributes to the field by synthesizing recent literature across various contexts, offering a conceptual basis for the development of more targeted, evidence-based programs aimed at improving adolescent happiness.